Implementasi Augmented Reality Berbasis Android dalam Pengenalan Rumah Adat Sulawesi Tenggara - Yanita, Putri Apri; Mardiawati, Mardiawati; Fakhrunnisaa, Nur (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2025)
The conservation of indigenous culture, particularly the traditional dwellings of Southeast Sulawesi, encounters obstacles owing to technological progress and changing preferences among younger demographics. This study created a Augmented Reality (AR) application for presenting traditional dwellings of Southeast Sulawesi utilizing the Multimedia Development Life Cycle (MDLC) methodology. This program enables users to obtain information regarding traditional houses via interactive 3D models, supplemented by text and voice, employing marker-based tracking technology. Testing was performed via Black Box Testing and User Acceptance Testing (UAT), which demonstrated that the application operates optimally on devices with a minimum of 3GB of RAM. User evaluation findings revealed a satisfaction level of 81.27%, classified as